THE CONCEPT OF LEARNING TO LEARN IN THE CONTEXT OF MUSIC EDUCATION - Rauduvaitė, Asta; Sun, Bo (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
In the context of lifelong learning, the importance of learning to learn is increasingly emphasised. There have been different views on defining the concept of learning to learn and the final definition has not been available yet. Researchers have made attempts to define and explore this concept in different areas. Sometimes they come from quite different epistemological and logical backgrounds. Learning to learn has been extensively analysed in the scientific literature and has been described in various ways. Using a literature review approach, this article presents a theoretical analysis on how the concept of learning to learn is understood in general music education, with the aim of discovering the specifics of learning to learn in this context. The role of planning, collaboration, reflection, and self-assessment in music education has also been identified in the study.